2020
DOI: 10.1507/endocrj.ej20-0011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of cytochrome P450 oxidoreductase deficiency: a nationwide survey in Japan

Abstract: Cytochrome P450 oxidoreductase deficiency (PORD) is a disorder of steroidogenesis that causes various symptoms such as skeletal malformations, disorders of sex development, and adrenal insufficiency. The aim of this study was to elucidate the clinical characteristics, especially age at diagnosis and treatment, of PORD from the perinatal period to adulthood in Japan. The first questionnaire was sent to 183 council members of the Japanese Society for Pediatric Endocrinology on 1 September 2018. The response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…(2) Cytochrome P450-oxidoreductase deficiency (PORD). PORD is a disorder of steroidogenesis that causes DSDs, adrenal insufficiency, and skeletal malformations [147]. It is an autosomal recessive disease typically diagnosed in neonates and children with ambiguous genitalia and/or skeletal abnormalities.…”
Section: Congenital Adrenal Hyperplasia In Female/adrenogenital Syndrmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Cytochrome P450-oxidoreductase deficiency (PORD). PORD is a disorder of steroidogenesis that causes DSDs, adrenal insufficiency, and skeletal malformations [147]. It is an autosomal recessive disease typically diagnosed in neonates and children with ambiguous genitalia and/or skeletal abnormalities.…”
Section: Congenital Adrenal Hyperplasia In Female/adrenogenital Syndrmentioning
confidence: 99%
“…It is responsible for the decreased activity of several P450 enzymes, including CYP21A2, CYP17A1, and CYP19A1, that are involved in adrenal and/or gonadal steroidogenesis [148]. In a study by Yatsuga et al [147] on the clinical characteristics of PORD in Japan, it is shown that in many cases, PORD can be diagnosed at <3 months of age. Hydrocortisone, as the primary treatment during infancy, can be used daily or just in stressful situations; however, because patients generally have mild-to-moderate adrenal insufficiency, some might be able to avoid the treatment.…”
Section: Congenital Adrenal Hyperplasia In Female/adrenogenital Syndrmentioning
confidence: 99%
“…1 A decreased POR function causes various symptoms, such as skeletal malformations, disorders of sex development, and adrenal insufficiency. 2,3 Skeletal malformations, such as joint contracture, radiohumeral synostosis, midface hypoplasia, and craniosynostosis, are distinctive clinical features of PORD, also known as Antley-Bixer syndrome, when associated with facial and cranial malformations and limb deformities. 1,3 The predicted cause of the malformations is impairment of cholesterol production and retinoic acid metabolism.…”
mentioning
confidence: 99%
“…The frequency of skeletal malformations ranges from 80% to 95%, 2,3,5 with joint contraction and radiohumeral synostosis being the most common. 2 Although recent studies have reported that 15% to 20% of PORD patients have scoliosis, 2,3,5 there were no reports of its severity or surgical cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation